Influence of PEDOT:PSS crystallinity and composition on electrochemical transistor performance and long-term stability - Kim, Seong-Min (Nat Commun, 2018)
Owing to the mixed electron/hole and ion transport in the aqueous environment, poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate)-based organic electrochemical transistor has been regarded as one of the most promising device platforms for bioelectronics. Nonetheless, there exist very few in-depth studies on how intrinsic channel material properties affect their performance and long-term stability in aqueous environments. Herein, we investigated the correlation among film microstructural crystallinity/composition, device performance, and aqueous stability in poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) films. The highly organized anisotropic ordering in crystallized conducting polymer films led to remarkable device characteristics such as large transconductance (∼20 mS), extraordinary volumetric capacitance (113 F·cm(−3)), and unprecedentedly high [μC(*)] value (∼490 F·cm(−1)V(−1)s(−1)). Simultaneously, minimized poly(styrenesulfonate) residues in the crystallized film substantially afforded marginal film swelling and robust operational stability even after >20-day water immersion, >2000-time repeated on-off switching, or high-temperature/pressure sterilization. We expect that the present study will contribute to the development of long-term stable implantable bioelectronics for neural recording/stimulation.